1995
DOI: 10.1046/j.1365-2648.1995.22020347.x
|View full text |Cite
|
Sign up to set email alerts
|

The Claybury community psychiatric nurse stress study: is it more stressful to work in hospital or the community?

Abstract: The Claybury community psychiatric nurse (CPN) stress study collected data on stress levels in 250 CPNs and 323 ward-based psychiatric nurses (WBPN) in the North East Thames region. Four out of 10 CPNs were found to be experiencing high levels of psychological distress on GHQ scores. Whilst both CPNs and WBPNs scored highly on scores of occupational burnout, especially on emotional exhaustion scores, WBPNs scored worse on emotional detachment from their patients and were achieving less personal fulfilment from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
126
2
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(147 citation statements)
references
References 16 publications
16
126
2
3
Order By: Relevance
“…among nurses population compared to 33.3 percent of the general population [11]. Gerald reported a prevalence rate of 34 percent the nurses, Fine, 41 percent [11,12]. Mums study results has shown that mental health problems in individuals with occupational burnout was significantly more [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…among nurses population compared to 33.3 percent of the general population [11]. Gerald reported a prevalence rate of 34 percent the nurses, Fine, 41 percent [11,12]. Mums study results has shown that mental health problems in individuals with occupational burnout was significantly more [13].…”
Section: Resultsmentioning
confidence: 99%
“…These are: somatic symptoms (items 1-7); anxiety/ insomnia (item [8][9][10][11][12][13][14]; social dysfunction (item 15-21)‚ and severe depression (item 22-28) [7].…”
Section: Methodsmentioning
confidence: 99%
“…This con®rms the ®ndings of the Claybury CPN Stress Study. 21 The compensation for this increase in stress is that nurses in the community have higher levels of job satisfaction and lower depersonalization burnout. The relationship between nursing grade and stress was slightly more complex.…”
Section: Discussionmentioning
confidence: 99%
“…Wall et al (1997), using the GHQ-12 on 11637 NHS staff, found psychiatric morbidity of 26.8% 3Age, experience and years overall, with 30% for male and 29% for female nurses. Caseness in the UK has been reported at 42% for early career mental health nurses (Kipping, 2000), 41% for CPNs (Fagin et al, 1995;1996), 39% for CMHT staff (Johnson et al, 2011), 38% for CMHT staff (Walsh et al, 2002); 35% (Edwards et al, 2000), 31% and 27.9% for WBPNs (Fagin et al, 1995;1996), 30% for CMHT staff (Wykes, Stevens & Everitt, 1997), 29% for mental health trust staff (Johnson et al, 2011). More recently, Mark and Smith (2012) surveyed nurses accessed at random via the Royal College of Nursing (hence a similar target group to the one in the present study, albeit not mental health nurses), using the Hospital Anxiety and Depression Scale (HADS) (Zigmond and Snaith, 1983), and found 27.3% of nurses to meet the 'clinical cut-off for anxiety and depression.'…”
Section: Prevalence Of Experience Of Mental Health Problems In Uk Mhnsmentioning
confidence: 99%